Local exact controllability of the diffusion equation in one dimension - Marius Beceanu (Abstract and Applied Analysis)
This paper establishes the local exact null controllability of the diffusion equation in one dimension using distributed controls in the case of the Dirichlet boundary value problem. Most of the techniques used in the course of the proof are borrowed from Barbu (2002).